Management of Impaired Carbohydrate Metabolism - A Review - Podlejska, Patrycja; Rozkosz, Katarzyna; Torbacka, Katarzyna; Sosin, Aleksandra; Bednarz, Wojciech; Wróbel, Zuzanna; Wróbel, Natalia; Jakubik, Olga; Torbacka, Maja; Kaczor, Joanna (Quality in Sport, 2025)
Introduction and purpose: Cushing Syndrome is a condition associated with a long-term elevated concentration of cortisol in the circulatory system. The most common type of Cushing syndrome is exogenous hypercortisolism, primarily iatrogenic, resulting from long-term glucocorticoid use, which affects multiple biological systems, including carbohydrate metabolism. The aim of our work was to present the mechanisms by which glucocorticoids affect carbohydrate metabolism and compile information on strategies for its management. Background: Glucocorticoids disrupt carbohydrate metabolism causing increased hyperglycemia, insulin resistance and diabetes mellitus. These adverse effects result from increased hepatic gluconeogenesis, reduced glycogenolysis, decreased expression of glucose transporter type 4 (GLUT4) and impaired insulin signaling. The most important factor to reduce the impact of glucocorticoids on carbohydrate metabolism is optimization of glucocorticoid therapy and ensuring proper patient surveillance. A comprehensive medical history and physical examination should be conducted prior to administration of long-term glucocorticoid therapy, with regular blood glucose monitoring throughout treatment. Another key factor is prompt implementation of appropriate pharmacologic therapy. Basal bolus insulin therapy is recommended for managing glucocorticoid-induced hyperglycemia (GIH), with metformin as the preferred oral agent. Equally significant is adopting a balanced diet and regular physical activity. Conclusion: Iatrogenic Cushing syndrome pose a significant problem both for patients and healthcare providers. Studies outline strategies for management of glucocorticoid-induced impaired carbohydrate metabolism, however further research is required to develop evidence-based guidelines to validate and optimize these approaches and improve the quality of life in patients with iatrogenic Cushing syndrome.